The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1590/s1415-43662004000100002
|View full text |Cite
|
Sign up to set email alerts
|

Distribuição da água no solo para o dimensionamento da irrigação por gotejamento

Abstract: O objetivo do dimensionamento de um sistema de irrigação por gotejamento é escolher adequadamente o "layout" e os componentes do sistema para promover a distribuição precisa da água (e fertilizante) para todas as plantas, ao longo do campo. Com vistas a este propósito, avaliaram-se as contribuições capazes de fornecer elementos básicos para o dimensionamento da irrigação por gotejamento, utilizando-se sondas de TDR. Assim, o estudo experimental foi dividido em duas partes; na primeira, tem-se o efeito de irrig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 19 publications
1
10
0
9
Order By: Relevance
“…Thus, as illustrated in Figure 3A, even two or three days after the water applications, the soil moisture gradient that is formed during the drip irrigations, as described in several papers (OR & COELHO, 1996, SOUZA & MATSURA, 2004, results in an increased moisture concentration at the central part of the wetted strip, that makes storage estimates based on the readings of the six tensiometers installed at this central portion (LAU) overestimate the actual storage value, as determined by the reading of all 24 tensiometers (LAB).…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Thus, as illustrated in Figure 3A, even two or three days after the water applications, the soil moisture gradient that is formed during the drip irrigations, as described in several papers (OR & COELHO, 1996, SOUZA & MATSURA, 2004, results in an increased moisture concentration at the central part of the wetted strip, that makes storage estimates based on the readings of the six tensiometers installed at this central portion (LAU) overestimate the actual storage value, as determined by the reading of all 24 tensiometers (LAB).…”
Section: Resultsmentioning
confidence: 68%
“…For the treatment submitted to a fixed irrigation interval, that is based on high frequency irrigation events, the combined effects of rain, soil moisture redistribution, and soil moisture extraction are not able to dissipate, significantly, the lateral soil moisture gradient that, according to OR & COELHO (1996) and SOUZA & MATSURA (2004), is formed during water application events. For this scenario, due to the persistence of lateral gradients of soil moisture , water storage estimates based on the twodimensional computation process (eq.…”
Section: Resultsmentioning
confidence: 99%
“…the vertical movement of water in the soil occurs without major restrictions, especially from a punctual source of water application, with low flows. SOUZA et al (2004) reported that the two main forces that govern the advancement of wetting front are the gravitational and matrix potential, and depending on the applied flow, occurs initially the acting on the gravitational potential at the expense of the matrix potential, forcing the water flow in the vertical direction. The wet surface area with buried emitters is lower compared to emitter placed on the soil surface, moreover, it has not been possible to observe a direct proportionality between the flow rates used and the wetted area, as featured previously on emitters positioned on the soil surface.…”
Section: Resultsmentioning
confidence: 99%
“…To do so, it must have a combination of the flow emitter and spacing in the system, so that it can be applied the water volume compatible with the culture water demand, in a region of soil profile in which this water is effectively used (SOUZA et al, 2004;LOPES et al, 2009;MAIA, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These often conflicting considerations require significant changes in irrigation system design and operation (relative to systems for maximal crop production) (Souza and Matsura, 2004). Among the available irrigation methods, drip irrigation offers key advantages for meeting contemporary water and nutrient management efficiency standards, since it allows accurate control of water supplied in small quantities directly to the root zone.…”
Section: Introductionmentioning
confidence: 99%